Exploring the working mechanism of graphene patterning by magnetic-assisted UV ozonation. Issue 40 (3rd October 2017) - Yue, Huan; Tao, Haihua; Wu, Yixuan; Su, Shubin; Li, Hao; Ni, Zhenhua; Chen, Xianfeng
Abstract : The working mechanism of graphene patterning by magnetic-assisted UV ozonation is explored. Abstract : When assisted with an inhomogenous vertical magnetic field, ultraviolet (UV) ozonation turns directional and is testified to be applicable to graphene patterning. Using a more cost-effective low-pressure mercury lamp, we further explore the underlying working mechanism by changing oxygen content, introducing reactive ozone or inert nitrogen molecules, and study the lateral under-oxidation impeded Dirac point shifts for a graphene field-effect transistor under UV irradiation. The paramagnetic oxygen molecule X 3 Σ−g accelerates toward graphene with the magnetic moment aligned parallel to the magnetic field. The O( 3 P) atoms, stemming from such a directional oxygen molecule, have a high initial velocity before being further accelerated, and therefore enhance the oxidation capability compared with those from weak diamagnetic ozone molecules. Intermolecular or atomic-molecular collisions between the high-speed oxygen molecules/atoms and the randomly moved weak diamagnetic molecules, including nitrogen and ozone, appear crucial in deteriorating graphene patterning by increasing the lateral under-oxidation. This study may shed light on our understanding of graphene patterning by magnetic-assisted UV ozonation.